Stacking beneficial haplotypes from the Vavilov wheat collection to accelerate breeding for multiple disease resistance - Jingyang Tong; Tarekegn, Zerihun T.; Jambuthenne, Dilani; Alahmad, Samir; Periyannan, Sambasivam; Lee T. Hickey; Dinglasan, Eric; Hayes, Ben (Springer, 2024)
Wheat production is threatened by numerous fungal diseases, but the potential to breed for multiple disease resistance (MDR) mechanisms is yet to be explored. Here, significant global genetic correlations and underlying local genomic regions were identified in the Vavilov wheat diversity panel for six major fungal diseases, including biotrophic leaf rust (LR), yellow rust (YR), stem rust (SR), hemibiotrophic crown rot (CR), and necrotrophic tan spot (TS) and Septoria nodorum blotch (SNB). By adopting haplotype-based local genomic estimated breeding values, derived from an integrated set of 34,899 SNP and DArT markers, we established a novel haplotype catalogue for resistance to the six diseases in over 20 field experiments across Australia and Ethiopia. Haploblocks with high variances of haplotype effects in all environments were identified for three rusts, and pleiotropic haploblocks were identified for at least two diseases, with four haploblocks affecting all six diseases. Through simulation, we demonstrated that stacking optimal haplotypes for one disease could improve resistance substantially, but indirectly affected resistance for other five diseases, which varied depending on the genetic correlation with the non-target disease trait. On the other hand, our simulation results combining beneficial haplotypes for all diseases increased resistance to LR, YR, SR, CR, TS, and SNB, by up to 48.1%, 35.2%, 29.1%, 12.8%, 18.8%, and 32.8%, respectively. Overall, our results highlight the genetic potential to improve MDR in wheat. The haploblock-based catalogue with novel forms of resistance provides a useful resource to guide desirable haplotype stacking for breeding future wheat cultivars with MDR.